Exosome-Derived LncRNAs in Lung Cancer - Fan, Tao; Sun, Nan; He, Jie (Frontiers in Oncology, 2020)
As extracellular vesicles, exosomes are released from most cells to perform cell-cell communication. Recent studies have shown that exosomes could be released into tumor microenvironment and blood to promote tumor progression through packaging and transmitting various bioactive molecules, such as cholesterol, proteins, lipids, miRNAs, mRNAs, and long non-coding RNAs (lncRNAs) to distant cells. LncRNAs have emerged as a major class of noncoding transcripts. A lot of LncRNAs have been discovered during the past few years of research on genomics. They have been proved to participate in various biological functions and disease processes through multiple mechanisms. In this review, we analyzed the role of exosome-derived lncRNAs in lung carcinogenesis and metastasis. We also highlight opportunities for clinical potential of exosomes with specific lncRNAs as biomarkers and therapeutic intervention in lung cancer.